2019
DOI: 10.1111/jog.14036
|View full text |Cite
|
Sign up to set email alerts
|

Proton beam therapy for recurrent ovarian carcinoma: A case report

Abstract: The efficacy and feasibility of proton beam therapy (PBT) for recurrent ovarian carcinoma had not been determined. Here we presented a case of recurrent ovarian carcinoma that was successfully treated with PBT. A 48-year-old woman who was diagnosed as left ovarian clear cell carcinoma underwent surgery without removal of two tumors. After achieving complete remission with postoperative chemotherapy, a recurrent tumor was found in the sigmoid colon, for which a colostomy was performed. Because second-line chemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…No case reports in gynecological cancer have reported severe complications related to PBT. Previous studies reported transient low-grade cystitis or fever only as complications [ 6 , 12 ]. A randomized phase IIB trial of esophageal cancer revealed that PBT was associated with fewer complications than intensity-modulated radiation therapy using conventional photons [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No case reports in gynecological cancer have reported severe complications related to PBT. Previous studies reported transient low-grade cystitis or fever only as complications [ 6 , 12 ]. A randomized phase IIB trial of esophageal cancer revealed that PBT was associated with fewer complications than intensity-modulated radiation therapy using conventional photons [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since 1954, when the medical use of protons was initially reported, PBT has been applied to various parts of the body, including the uvea, skull base, and spine [1,9,10]. In the gynecological field, the clinical use and efficacy of PBT have mainly been reported for cervical carcinoma [3][4][5], low-grade endometrial stromal sarcoma [11], and solitary recurrent epithelial ovarian cancer [12]. Only one case report of the vaginal recurrence of endometrial carcinoma treated with PBT is available in the literature, which describes the complete regression of the tumor; however, there was a complication of grade 1 cystitis.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, antibody guided 90 Y has been explored in the context of ovarian cancer, but it did not proceed from phase III clinical trials ( 12 , 13 ). Alternative types of radiotherapy options that have been explored for ovarian cancer include proton beam therapy and carbon ion therapy with successful outcomes in two case reports of patients with recurrent ovarian cancer ( 14 , 15 ).…”
Section: Introductionmentioning
confidence: 99%